Screening and Prevention of Cervical Cancer in the World - Vargas-Hernández Victor Manuel (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2017)
Cervical cancer is the leading cause of morbidity and mortality among gynecological cancers worldwide. Cervical cancer is the main cancer found in developing countries. There are risk factors for cervical cancer worldwide, mainly persistent infection of high risk HPV, especially genotypes 16 and 18 viruses. Cervical cancer prevented when precursor lesions detected and treated before they develop cancer. Cervical cancer is preventable, and effective screening programs reduce morbidity and mortality associated with this type of cancer; however, the programs vary according to socio-economic conditions of each country, which reflected in the increased incidence, morbidity, mortality from cervical cancer in developing countries.